2017
DOI: 10.1016/j.bios.2016.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and sensitive detection of bisphenol a from serum matrix

Abstract: Bisphenol A (BPA) is an endocrine disrupting compound that may have adverse developmental, reproductive, neurological, and immune system effects. Low-level exposure to BPA is ubiquitous in human populations due to its widespread use in consumer products. Therefore, highly sensitive methods are needed to quantify BPA in various matrices including water, serum, and food products. In this study, we developed a simple, rapid, highly sensitive and specific sensor based on an aptamer probe and AC electrokinetics cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 45 publications
(15 reference statements)
0
28
0
Order By: Relevance
“…Indeed, diverse exposures to modern environmental factors are increasingly recognized as a risk factor for neurodevelopmental disorders (reviewed in [51]), including pesticides, various components of air pollution (diesel exhaust, NO2, heavy metals), phthalates, polychlorinated biphenyls (e.g., BPA), and even dietary components such as saturated fats and common food allergens (e.g., gluten, casein) [52] (see Table 1). Air pollution, of which diesel exhaust is a primary toxic component [53,54] is the 4 th leading cause of mortality worldwide [55,56] and poses a serious and growing health concern for countries where industrial growth is exponential.…”
Section: Environmental Factors Affecting Microglial Developmentmentioning
confidence: 99%
“…Indeed, diverse exposures to modern environmental factors are increasingly recognized as a risk factor for neurodevelopmental disorders (reviewed in [51]), including pesticides, various components of air pollution (diesel exhaust, NO2, heavy metals), phthalates, polychlorinated biphenyls (e.g., BPA), and even dietary components such as saturated fats and common food allergens (e.g., gluten, casein) [52] (see Table 1). Air pollution, of which diesel exhaust is a primary toxic component [53,54] is the 4 th leading cause of mortality worldwide [55,56] and poses a serious and growing health concern for countries where industrial growth is exponential.…”
Section: Environmental Factors Affecting Microglial Developmentmentioning
confidence: 99%
“…Several methods for BPA detection have been investigated to obtain a high‐performance technique that can detect BPA at low concentrations. BPA‐contaminated samples including drinking water, food, serum, and urine were examined by using methods such as gas chromatography (GC), high‐performance liquid chromatography (HPLC), immunoassays, and electrochemical techniques with limits of detection (LODs) ranging from 10 −15 to 10 −9 molL −1 . A recent study reported an MIP application involving silica mesopheres in conjunction with spectroscopic detection, which offered a cheap and reliable means to determine BPA contamination with an LOD of 0.5 ppm (2.2 μ m ) .…”
Section: Figurementioning
confidence: 55%
“…The BPA–dengue virus complex can lead to the maximization of the available sites for BPA during polymerization though surface binding, leading to dramatically lower LODs. This MIP detection method approaches the femtomolar level of the most sensitive BPA detection method currently reported in the literature . Despite being marginally less sensitive, a key advantage of our approach is its low cost, owing to the mass availability of reagents, which should afford a high accuracy, cost‐effective sensor solution.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…ACEK includes DEP, ACEO and ACET effect. With planar electrodes, ACEO and ACET effects induce rotating vortices above electrodes that carry molecular analytes toward the electrodes, and effective concentration of molecule analytes for detection has been demonstrated using either ACEO or ACET effect . As the working fluid in this work is rather conductive (∼1 S/m), ACEO effect can be ruled out as a contributing factor in DNA enrichment.…”
Section: Resultsmentioning
confidence: 86%